Ethnographic Perspectives to Teaching and Learning in Multilingual Contexts - Ana María Relaño Pastor (FahrenHouse, 2019)
This special issue addresses the organization of teaching and learning in a variety of multilingual schooling contexts from different critical ethnographic perspectives (i.e.: critical sociolinguistic ethnography, linguistic anthropology, and language socialization). By analyzing a range of educational settings in Spain, the U.S., the U.K., Argentina, and Guatemala, the articles establish a dialogue with different ethnographically-oriented studies to understand the relationship between situated communicative practices, language policies, language ideologies, dominant discourses about bi-multilingualism, and wider social, cultural and economic processes.